Pregnancy outcomes in women with rheumatoid arthritis: an 11-year French nationwide study - Jérôme Drouin; Alain Weill; Rosemary Dray-Spira; Laura Pina Vegas (RMD Open)
Background Rheumatoid arthritis (RA) can affect women of childbearing age. The management of patients with RA during pregnancy has evolved over the past decades, especially with the availability of new therapeutic molecules.Objectives To describe pregnancy in women with RA, to compare pregnancy outcomes with those of women in the general population and to compare pregnancy outcomes in women with active and inactive RA.Methods Using the French National Health Data System, we identified all pregnancies ending between 2010 and 2020 in patients with and without RA. Characteristics were described. Active RA was defined by conventional synthetic/biological/targeted synthetic disease-modifying antirheumatic drug initiation, systemic or intra-articular corticosteroid administration and/or RA-related hospitalisation. Pregnancy outcomes were compared computing multivariable logistic marginal regression model using generalised estimating equation (GEE).Results We included 11 792 RA and 10 413 681 non-RA pregnancies. Among RA pregnancies, 74.5% ended in live births and 0.4% in stillbirths. RA pregnancies resulted more frequently in preterm births (adjusted OR (ORa) 1.84; 95% CI 1.69 to 2.00) and very preterm births (ORa 1.43; 95% CI 1.20 to 1.71), low birth weight (ORa 1.65; 95% CI: 1.52 to 1.90), caesarean section (ORa 1.46; 95% CI 1.38 to 1.55) and pregnancy-related hospitalisation (ORa 1.30; 95% CI 1.22 to 1.39). Disease activity decreased during pregnancy. Active RA had higher rates of prematurity (ORa 2.02; 95% CI 1.71 to 2.38), small for gestational age (ORa 1.53; 95% CI 1.28 to 1.83) and caesarean section (ORa 1.25; 95% CI 1.11 to 1.40) than non-active RA.Conclusion Pregnancies in women with RA were associated with more adverse outcomes, especially if the disease was active. These findings should encourage physicians to closely monitor RA during this crucial period.